2018
DOI: 10.1002/chir.22854
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids as chiral derivatizing agents for antiproliferative substituted N‐benzyl isoindolinones

Abstract: The absolute configurations of the diastereomers of novel amino acid ester derivatives of 2,3-substituted isoindolinones, which are known as apoptosis activators due to their ability to inhibit the MDM2-p53 PPI, were assigned using NMR and computational methods. Procedures for diastereomer separation and determining the absolute configuration were developed to perform the study. The high significance of N-benzyl fragment for the determination of the diastereomer absolute configuration by NMR methods was establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…We showed that indolinone derivatives can effectively induce apoptosis of cancer cells by the example of U2OS (human osteosarcoma) and HEK293T (human embryonic kidney) cell lines with different p53 status, at the same time the mechanism of the drugs was confirmed using recombinant protein models of p53 and MDM2 [9,12,18]. On the other hand, substances based on the indolinone scaffold confirmed their effectiveness in preventing and/or slowing down the development of multidrug resistance; promising results were obtained not only in experiments in cells, but also in xenografts [22,23].…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…We showed that indolinone derivatives can effectively induce apoptosis of cancer cells by the example of U2OS (human osteosarcoma) and HEK293T (human embryonic kidney) cell lines with different p53 status, at the same time the mechanism of the drugs was confirmed using recombinant protein models of p53 and MDM2 [9,12,18]. On the other hand, substances based on the indolinone scaffold confirmed their effectiveness in preventing and/or slowing down the development of multidrug resistance; promising results were obtained not only in experiments in cells, but also in xenografts [22,23].…”
Section: Resultsmentioning
confidence: 87%
“…The library was based on classes of compounds studied in our laboratory, which in in vitro experiments showed activity comparable to the activity of substances at the stage of clinical trials [18,19] (Fig. 1).…”
Section: Metarials and Methodsmentioning
confidence: 99%
“…In fact, calculations for (C S* ,S S* )-4d stable conformers indicate that the above-mentioned nuclei experience a significantly different magnetic environment which would result in a downfield shift of their resonances both in 1 H and 13 C NMR spectrum (see Table S1 for details). 12…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It should be noted that in the case of rigid targets, such as Mdm2 or AMPK, docking clearly proves its effectiveness and high predictive power. However, the structure of P-gp has a number of fundamental differences.…”
Section: Introductionmentioning
confidence: 83%